Uncovering Food Poverty in Ireland : A Hidden Deprivation - Drew, Michael (Book collections on Project MUSE., 2022)
Offering a much-needed analysis of the overlooked crisis of food poverty in Ireland, this book brings together the complex picture emerging from interviews with users of food aid, explores the international landscape of food poverty and what action should be taken.